Early effect of Medicare Shared Savings Program accountable care organization participation on prostate cancer care. Issue 3 (20th October 2017) - Borza, Tudor; Kaufman, Samuel R.; Yan, Phyllis; Herrel, Lindsey A.; Luckenbaugh, Amy N.; Miller, David C.; Skolarus, Ted A.; Jacobs, Bruce L.; Hollingsworth, John M.; Norton, Edward C.; Shahinian, Vahakn B.; Hollenbeck, Brent K.
Abstract : BACKGROUND: Accountable care organizations (ACOs) can improve prostate cancer care by decreasing treatment variations (ie, avoidance of treatment in low‐value settings). Herein, the authors performed a study to understand the effect of Medicare Shared Savings Program ACOs on prostate cancer care. METHODS: Using a 20% Medicare sample, the authors identified men with newly diagnosed prostate cancer from 2010 through 2013. Rates of treatment, potential overtreatment (ie, treatment in men with a ≥75% chance of 10‐year mortality from competing risks), and Medicare payments were measured using regression models. The impact of ACO participation was assessed using difference‐in‐differences analyses. RESULTS: Before implementation of ACOs, the treatment rate was 71.8% (95% confidence interval [95% CI], 70.2%‐73.3%) for ACO‐aligned beneficiaries and 72.3% (95% CI, 71.7%‐73.0% [ P  = .51]) for non‐ACO‐aligned beneficiaries. After implementation, this rate declined to 68.4% (95% CI, 66.1%‐70.7% [ P  = .017]) for ACO‐aligned beneficiaries and 69.3% (95% CI, 68.5%‐70.1% [ P <.001]) for non‐ACO‐aligned beneficiaries. There was no differential effect noted for ACO participation. The rate of potential overtreatment decreased from 48.2% (95% CI, 43.1%‐53.3%) to 40.2% (95% CI, 32.4%‐48.0% [ P  = .087]) for ACO‐aligned beneficiaries and increased from 44.3% (95% CI, 42.1%‐46.5%) to 47.0% (95% CI, 44.5%‐49.5% [ P  = .11]) for non‐ACO‐aligned beneficiaries. These changes resulted in a significant relative decrease in overtreatment of 17% for ACO‐aligned beneficiaries (difference‐in‐differences, 10.8%; P  = .031). Payments were not found to be differentially affected by ACO alignment. CONCLUSIONS: The treatment of prostate cancer and annual payments decreased significantly between 2010 and 2013, but ACO participation did not appear to impact these trends. Among men least likely to benefit, Medicare Shared Savings Program ACO alignment was associated with a significant decline in prostate cancer treatment. Cancer 2018;124:563‐70 . © 2017 American Cancer Society . Abstract : Accountable care organizations (ACOs) have the potential to reduce treatment variations in patients with prostate cancer through avoidance of treatment in low‐value settings, in an effort to improve quality and decrease wasteful spending. In this analysis of Medicare data, the authors report that overall treatment rates appear to be similar among ACO‐aligned and non‐ACO‐aligned beneficiaries. However, among men least likely to benefit from treatment (ie, potential overtreatment), ACO alignment is associated with a 17% decrease in initial treatment.